Strengthening Roles of Pesantren in The Solving Problems Management of Coronavirus 19 - Fathimatuz Zahra Anis (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
Coronavirus 19, is a new virus that can infect anyone indiscriminately. This virus, not only as a virus that makes various layers of society experience anxiety, but also creates a point of introspection for all levels of society. In this process of mass introspection, pesantren has a strengthening role in order to provide peace to society and also as a source of community support in action. Because there are so many new regulations related to Covid 19 that are being debated in the religious field. This article will discuss the role of strengthening Islamic boarding schools in solving problems management of coronavirus 19. This research is a qualitative research by collecting library data and news related to the public's response to Covid 19. This article will discuss the role of strengthening Islamic boarding schools in various problems related to Covid 19 in society. This question will be answered using the theory of the role of reinforcement originating from pesantren which supports and has a significant impact on society.